Aortic Arch Floating Thrombus Complicated by Distal Embolization in a Patient with Malignancy - Konstantinos Tigkiropoulos; Dimitrios Karamanos; Marianthi Tympanidou; Nikolaos Saratzis; Ioannis Lazaridis (Case Reports in Vascular Medicine)
Free floating thrombus of aortic arch in a minimally atherosclerotic or nonaneurysmal aorta is a rare disease entity which carries a potential risk of distal embolization with catastrophic consequences. We present the case of a 52-years-old patient with ovarian cancer and aortic arch floating thrombus who initially managed with low molecular weight heparin and eventually undergone surgical thrombectomy of left external iliac and common femoral artery due to acute ischemia of left lower leg.